Evaluating the Effectiveness of Pfizer, AstraZeneca, and Sinopharm Vaccines Against COVID-19 in Iraq: A Cross-Sectional Study of Vaccine Efficacy and Symptom Severity - Yasir W. Issa; Shahlaa M. Salih (Journal of Madenat Alelem University College, 2024)
Background: In response to the COVID-19 pandemic, the rapid development of vaccines targeting the SARS-CoV-2 virus has been pivotal. These vaccines work by triggering antibody production to neutralize the virus. This study evaluates the efficacy of available COVID-19 vaccines in Iraq, contributing to public health knowledge in the region.Methods: A cross-sectional analysis was performed using 1,233 Iraqi participants vaccinated with one of the available vaccines in Iraq, including Pfizer, AstraZeneca, or Sinopharm, and exposed to COVID-19 infection after their immunization. Most clinical evaluations were conducted with all participants.Results: The study found that Pfizer vaccine recipients predominantly experienced mild COVID-19 symptoms, with fewer cases of moderate or severe symptoms. Those vaccinated with AstraZeneca mainly reported mild to moderate symptoms, with fewer severe or asymptomatic cases. Sinopharm recipients generally showed no symptom frequencies, followed by mild and moderate cases with rare severe symptoms. In contrast, unvaccinated individuals primarily exhibited moderate to severe symptoms, with fewer mild or asymptomatic cases.Conclusions: The study suggests that COVID-19 vaccines are more effective at preventing severe disease outcomes, such as hospitalization and death, than mild or asymptomatic infections. In Iraq, Sinopharm and Pfizer vaccines were observed to be more effective in reducing severe COVID-19 cases and hospitalizations compared to the AstraZeneca vaccine and unvaccinated individuals.